The Mediating Role of Career Adaptability on Graduate Employability among Students in the Malaysian Technical University Networks (MTUN) - Wong, Reynold; Ummi Naiemah Saraih (Journal of Communication in Scientific Inquiry (JCSI), 2024)
This study aims to evaluate the relationship between self-efficacy (SE), soft skills, and personality traits on perceived graduate employability (GE) among final-year students in Malaysian Technical University Networks (MTUN), with career adaptability (CA) as a mediating variable. The research will employ a quantitative approach by analyzing the collected data using the Statistical Package for the Social Sciences (SPSS). Data will be collected through a structured questionnaire distributed to a sample of 370 undergraduate students from various MTUN universities. The questionnaire will assess students’ perceptions of SE, soft skills, personality traits, CA, and perceived GE. Statistical analysis will be used to determine the relationships between these factors. Additionally, the mediating role of CA will be tested in this study. By identifying key factors that contribute to employability, the research aims to inform educational strategies, leading to more effective training programs, enhanced career services, and targeted interventions. Ultimately, this study seeks to contribute to the broader goal of improving GE and ensuring that higher education institutions produce graduates who are well-equipped to succeed in their careers. Kajian ini bertujuan menilai hubungan antara kecekapan kendiri (SE), kemahiran insaniah, dan ciri-ciri personaliti terhadap kebolehpasaran graduan (GE) seperti yang dirasai oleh pelajar tahun akhir di universiti dalam Rangkaian Universiti Teknikal Malaysia (MTUN), dengan kebolehsuaian kerjaya (CA) sebagai pemboleh ubah perantara. Kajian ini menggunakan pendekatan kuantitatif dengan menganalisis data menggunakan Perisian Statistik untuk Sains Sosial (SPSS). Data akan dikumpulkan melalui soal selidik berstruktur yang diedarkan kepada sampel 370 pelajar sarjana muda dari pelbagai universiti MTUN. Soal selidik ini akan menilai persepsi pelajar terhadap SE, kemahiran insaniah, ciri-ciri personaliti, CA, dan GE. Analisis statistik akan digunakan untuk menentukan hubungan antara faktor-faktor ini, dan peranan perantaraan CA juga akan diuji. Dengan mengenal pasti faktor utama yang menyumbang kepada kebolehpasaran, kajian ini bertujuan untuk memperkukuh strategi pendidikan, menghasilkan program latihan yang lebih berkesan, perkhidmatan kerjaya yang lebih baik, dan intervensi yang disasarkan. Akhirnya, kajian ini berhasrat menyumbang kepada matlamat yang lebih luas iaitu meningkatkan GE dan memastikan institusi pengajian tinggi melahirkan graduan yang bersedia untuk berjaya dalam kerjaya mereka.